Hand to God: The Irreverent Laughter of Robert Askins - “Laugh, motherfuckers, that shit’s funny” (Askins 31) - Marianne Drugeon (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2019)
This article aims at defining the laughter provoked by the play Hand to God written by American playwright Robert Askins in 2011. This dark comedy uses the classical tools of humour, as analysed by Henri Bergson in his essay on laughter, but it creates a desperate atmosphere of mental and physical violence, which reminds of the tactics of British in-yer-face theatre. Askins aims at displaying the taboos and denouncing the hypocrisy of the American society in general, and more particularly that of Christian congregations faced to the sexuality of teenagers. The spectators’ reactions are a complex combination of laughter and unease, as Askins dares them to laugh as they cringe. But those reactions also depend on the conditions of production, which have greatly varied from Off-Broadway to Broadway, and from New York to London and Paris.